DIGITAL CAPACITANCE METER - Indra Budi Cahya Ardi; Luyung Dinaini Skom, MM. (Jurnal Sistem Komputer, 2002)
This thesis explores the design, build, analyze the work circuit, and test a series ofDigital Capacitance Meter. It works by using two monostable multivibrator as shownon the input from the output through seven segment indicator. As the source voltageused 9-volt battery.This tool is used to determine condition and capacity of a capacitor in the variousunits, namely: Pikko farad (pF), nano-farad (nF), micro and milli farad farad (MF).